Analysis and interpretation of financial statement (a case study on NOL) - Ho, Seng Kwong (2014)
The financial statements issued by a firm are used by various parties to evaluate the firm’s financial performance. The users include management, investors, shareholders and creditors. The basic objective of financial statement is to provide users with information useful for economic decision making.